Resilience Under Pressure: Application of CRes Index to Monitor Coral Ecosystem Shifts in Jaboi, Aceh Post-Mass Bleaching Events - Nadia Aldyza; Afkar Afkar (Journal Omni-Akuatika, 2026)
This study assessed the resilience of coral reef ecosystems in the coastal waters of Jaboi, Sabang City, Weh Island, conducted in August 2025. The study area is an open marine zone that has not yet been designated as a marine protected area, highlighting the urgency of evaluating ecosystem resilience as a scientific basis for future conservation planning. Data collection was conducted using six parallel transects installed along the coastline at depths of 3 m and 7 m. Coral cover, turf algae, Crustose Coralline Algae (CCA), and rubble were recorded using 50 m line transects combined with underwater video analysis, while the density of blue sea stars (Linckia laevigata) and sea urchins was assessed using belt transects (100 m²). The results indicated that shallow waters exhibited higher live coral cover, greater CCA presence, and higher abundance of L. laevigata, reflecting a more stable ecosystem with strong recovery potential. In contrast, deeper waters showed increased dominance of turf algae and higher sea urchin density, suggesting emerging ecological pressures despite remaining within the high-resilience category. Differences in substrate quality between depths were identified as a key factor influencing benthic community structure. Overall, the coral reefs of Jaboi demonstrate relatively high resilience; however, early signs of ecological stress emphasize the need for continuous monitoring and proactive management. The findings support the use of the CRes Index as an effective tool for reef resilience assessment and provide essential baseline data to inform conservation zoning, restoration initiatives, and sustainable coastal management in Indonesia.